Isolation and molecular identification of Lumpy Skin Disease (LSD) virus from infected cattle in Bangladesh (Bangladesh Journal of Livestock Research, 2020)
Lumpy Skin Disease (LSD) is a new disease of cattle in Bangladesh. It is endemic in Africa but through the last few years disease beings to spread to other countries of the world. The disease was widely spreaded in the many other countries in Asia and some parts of Europe. In Bangladesh, the disease was first time detected in April 2019, in southern part and then continued to spread all over the country.The disease caused enormous economic losses causing cutaneous and internal lesions, affecting milk production, hide quality and in some cases death of infected animal. LSD suspected samples were collected from different areas of the country during the period from July 2019 to January 2020. In this study, a total of 36 clinically suspected LSD samples of skin crustnodules, pus and ocular discharge were collected. Samples were examined by the published PCR protocol for LSD virus, GPV and SPV. Around 78% samples were found positive for LSD virus in PCR test. LSD virus was also identified from pus and ocular discharge of infected cattle. The virus can grow in the lamb testicular cell and clinically the disease is characterized by distinctive nodular lesions mostly on the skin of the affected animals.The results indicated that the LSD virus is circulating in the outbreak are as and is an emerging transboundary cattle disease in Bangladesh.Bang. J. Livs. Res. Vol. 26 (1&2), 2019: P. 15-20